The effects of water immersion on recovery in Australian football - Elias, G. P. (2013)
Participation in a physically demanding team sport, such as Australian football (AF), can result in post-exercise physical performance decrements as well as increases in psychometric measures, muscle damage and inflammation. The use of both cold water immersion (CWI) and contrast water therapy (CWT) as a means of post-exercise recovery is becoming more prevalent in the team sport environment. Both modalities are utilised in an attempt to enhance physical performance recovery while reducing perceived muscle soreness and fatigue. Although increasing in popularity, conflicting evidence exists regarding their effectiveness. Comparisons within the same team sport population are lacking, while little information on the efficacy of either intervention exists in AF. Therefore, the effects of a single 14 min exposure of both CWI and CWT on restoring repeat 20 m sprint time, jump performance and psychometric measures was investigated following AF training (Study 1) and an AF match (Study 2). The effects of both modalities post-match on moderating the appearance of markers of muscle damage and inflammation was also investigated (Study 3). Australian football training and match participation reduced repeat sprint, countermovement and squat jump performance and increased perceptions of fatigue and muscle soreness. Match participation also greatly increased inflammatory and muscle damage markers. Both CWI and CW were more successful than a passive recovery at attenuating decrements in physical performance and reducing exercise induced increases muscle soreness, fatigue and markers of muscle damage, with CWI being the most effective. Neither CWI nor CWT altered the postexercise inflammatory response and therefore most likely had no effect on blunting the inflammatory pathways involved in muscle repair. Results demonstrate that AF participation leads to post-exercise declines in physical performance, an acute phase inflammatory response, muscle damage and heightened perceptions of soreness and fatigue. It was established that in well trained AF players, both modalities were more effective at attenuating these changes than a passive recovery with CWI being more effective. These findings add to the body of knowledge regarding the use and efficacy of CWI and CWT in team sport and would be of benefit to team sport athletes/coaches in decreasing any confusion regarding their use and in helping them to determine the best modality for their recovery needs.